Interleukin-1A May Illuminate Differential Effects of the Retinal Artery Caliber in HIV Patients - Lukman Edwar; Ibnu Agus Ariyanto; Selita Agnes Tanudjaja; Ratna Sitompul; Silvia Lee; Patricia Price (Molecular and Cellular Biomedical Sciences, 2021)
Background: Retinal artery caliber (RAC) is narrower in human immunodeficiency virus (HIV)-infected patients beginning antiretroviral therapy (ART). We aimed to assess associations between variations in genes encoding inflammatory mediators and natural killer receptors and retinal artery caliber (RAC) in HIV patients beginning ART.Materials and Methods: Seventy-nine HIV positive patients beginning ART with less than 200 cluster of differentiation (CD) 4 T-cells/μL were recruited. Examinations were performed before ART (V0) and at months 3, 6 and 12 (V3, V6, V12). The study was approved by ethics committees and informed consent was obtained from each subject.Results: Right and left RAC of the HIV patients were narrower than healthy controls (p=0.016 for right RAC) and narrowed further on ART, but demographic associations with the right and left RAC were not identical. Here we show that polymorphisms in genes encoding NK receptors or TNF activity had no significant impact, but right RAC was associated with carriage of allele 2 at IL1A+4845 (p=0.037 after 12 months on ART).Conclusion: Overall the paradoxical reduction in the RAC in HIV patients responding to ART was not modified by genotypes known to affect NK cell function or TNF responses, but IL1A genotype may modify the decline in the right RAC.Keywords: anti-retroviral therapy, CMV, HIV, IL1A, retinal artery caliber